Initiation into the mysteries of Augustus: the Liberalia and the Forum Augustum = Inicjacja w misteria Augusta: Liberalia i Forum Augustum - Vuković, Krešimir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper uses the theoretical framework of cultural memory to explain Augustus` construction of Forum Augustum. The construction of Forum Augustum was a central project in the "princeps"; programme as it presented his own version of Roman history giving a special place to his family and generals closest to this vision of the ideal Roman. At the same time, the evidence for Augustus` religious reforms shows a decisive ruler who was very involved with the intricacies of Roman religion.
Keywords: Augustus Gaius Julius Caesar (63 BC-14 AD); Roman religion; religious reform; Forum Augustum; initiation; Liberalia; August Gajusz Juliusz Cezar (cesarz rzymski; 63 p.n.e.-14 n.e.); religia rzymska; reformy religijne; inicjacja